Using sprint velocity decrement to enhance acute sprint performance - Cochrane, D. J.; Monaghan, D. (The Journal of Strength and Conditioning Research, 2021)
Acute sled towing has the capability to elicit a potentiation. Currently, sled loading is determined from body mass (BM) percent. However, it may be more relevant to use a percentage of maximal sprint reduction to determine an individual's load. The purpose of this study was to determine if individualizing sled loads at 35 and 55% reduction in velocity would improve 20-m sprint performance. In addition, electromyography (EMG) was assessed to determine if any sprint-related improvements in velocity were due to changes in neural excitation. Twelve senior club male rugby union players performed familiarization and 2 sled towing sessions using a randomized, cross-over, and counterbalanced design. Testing sessions involved: baseline unresisted 20-m sprints, resisted sprint (35 and 55% reduction in velocity), and unresisted 20-m sprints at 2, 4, 6, 8, 12, and 16 minutes. The sled load to reduce maximal velocity by 35% significantly improved 20-m velocity (p <0.05, effect size [ES] = 0.21) compared with the heavier sled load (55% reduction in maximum velocity). A significant decline in sprint velocity occurred at 12 minutes (p < 0.01, ES = -0.61) and 16 minutes (p < 0.01, ES = -0.45) compared with baseline velocity. Other time intervals reported trivial small nonsignificant changes in sprint velocity (p >0.05). There was no significant change in EMG. Reducing sprint velocity provides an alternate method to determining sprint loading. Nonetheless, a greater range of reduced sprint velocity is required to assess if it is more effective than using BM percent procedure.